2004
DOI: 10.1002/ppul.20046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of airway function in young children with asthma: Comparison of spirometry, interrupter technique, and tidal flow by inductance plethsmography

Abstract: The assessment of airway function in young children requires adaptation of techniques designed for adults and/or application of techniques that do not require complex respiratory maneuvers. We sought to assess two methods of measuring airway function: time to peak expiratory flows as a ratio of expiratory time (T(PTEF)/T(E)), derived from respiratory inductance plethysmography, and total respiratory resistance by the interrupter technique (Rint), both obtained during quiet tidal breathing. Both techniques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…15 Other studies suggesting closer relationships between the R int and FEV 1 have concentrated on population rather than individual data sets. 4,16 Unless otherwise stated, all data are presented as mean (standard deviation). FEV 1 , forced expiratory volume in 1 sec; R int , interrupter resistance; SI, sensitivity index; GM, geometric mean.…”
Section: Discussionmentioning
confidence: 99%
“…15 Other studies suggesting closer relationships between the R int and FEV 1 have concentrated on population rather than individual data sets. 4,16 Unless otherwise stated, all data are presented as mean (standard deviation). FEV 1 , forced expiratory volume in 1 sec; R int , interrupter resistance; SI, sensitivity index; GM, geometric mean.…”
Section: Discussionmentioning
confidence: 99%
“…69 In the latter group, a correlation coefficient of 0.73 was found for baseline values of spirometry and R int . 71 R int has been used in conjunction with other measures to evaluate bronchodilator response in asthmatic children. As to discriminating capacity, R aw , R5, R int , and X5 were found to be useful, with positive predictive values of 84%, 74%, 82%, and 76%, respectively.…”
Section: Measurement Of Airway Resistance By the Interrupter Techniquementioning
confidence: 99%
“…In studies involving asthma patients, the Rint technique was shown to be accurate in measuring such a response. (15)(16)(17)(18)(19) The objectives of the present study were to measure airway resistance with the Rint technique in children and adolescents with CF and to determine whether the values obtained correlated with spirometric parameters, as well as to evaluate the accuracy of the Rint technique in determining the airway response to a bronchodilator. Instrumentation Inc., Louisville, CO, USA).…”
Section: Introductionmentioning
confidence: 99%